Multidimensional comparative analysis of the European Union countries in the field of sustainable development - Bartłomowicz, Tomasz; Cheba, Katarzyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The subject of the study is a comparative analysis of the level of sustainable development of the European Union. The basis of the study was the data collected in the Eurostat database, which the European Commission uses to monitor the implementation of the objectives of EU Sustainable Development Strategy. In order to determine similarities and differences in the level of development of EU countries in the study area, a method of multidimensional scaling was used. The obtained results allowed to identify similar as well as different countries because of their designated sizes. There were also identified countries whose sustainability is the closest to the object of reference and those whose previous development is similar to antipattern. In the calculations the environment and packages of R program were used
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 476, s. 118-126
Keywords: Eurostat; multidimensional scaling; sustainable development indicators; skalowanie wielowymiarowe; wskaźniki zrównoważonego rozwoju